PENGARUH DOSIS KOMPOS TANDAN KOSONG KELAPA SAWIT YANG DI PERKAYA ABU BOILER TERHADAP SIFAT KIMIA TANAH ULTISOL, PERTUMBUHAN, PRODUKSI, KADAR HARA DAN LOGAM BERAT PB PADA TANAMAN SAWI (Brassica juncea L.) - Sri Mulyani (UIR Press, 2019)
The purpose of this study was to study the effect of improved quality of oil palm empty fruit bunch compost on the chemical properties of ultisol soil, growth, production, nutrient content, and heavy metals Pb in mustard plants. This study was conducted from March 2015 to January 2016. The study was conducted with a single factor experiment with 13 treatments and 3 replications, so that 39 unit experiments were obtained which were placed into a Completely Randomized Design. The treatment consisted of 4 tankos compost, namely tankos compost. The beginning of the composting process was added to boiler ash at 4 dosage levels, namely 0% (K1), 15% (K2), 25% (K3), 35% (K4), then given into the soil with 3 dose levels, namely 10 tons/ha (D1), 20 tons/ha (D2), 30 tons/ha (D3). Observational data was analyzed statistically using the Analysis of Variance (ANOVA) with the F test at an alpha level of 5%. If the treatment is found a significant effect, it will be continued with the Duncan Multiple Range Test (DMRT) at the alpha level of 5%. The results showed that the various doses of oil palm empty fruit bunch compost plus added boiler ash at the beginning of the composting process at the same dose had a significant effect on increasing Ca-dd, Mg-dd, K-dd soils and decreasing Al-dd soils, plant height, number of leaves, leaf width and K content of mustard plants. The best dose that can produce the highest production was the composting process treatment that was added with 15% boiler ash at a dose of 10 tons/ha (K1D1). In the Pb heavy metal content was not measurable, so the plant was suitable for consumption.